2012
DOI: 10.4048/jbc.2012.15.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of High Expression of ER-beta in Surgically Treated ER-Positive Breast Cancer Following Endocrine Therapy

Abstract: PurposeThis study evaluated estrogen receptor (ER)-beta mRNA and ER-beta protein expression and its prognostic implications in hormone receptor-positive breast cancer.MethodsParaffin sections from 139 hormone receptor-positive breast cancer cases were prepared. The expression of ER-beta mRNA and protein were analyzed by branched-chain assay and immunohistochemistry (IHC), respectively.ResultsThe Allred score of ER-beta IHC was correlated with smaller tumor size (p=0.043), the Allred score of ER-alpha IHC (p<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…In the current study, there were notably positive correlations between Ki-67 and Ktrans values. Consistent with our results, Kim et al found that the Ktrans values in breast cancer with Ki-67 overexpression were significantly higher in patients with low expression of Ki-67 [38]. However, unlike Kim et al’s study, there was no correlation between Kep value and Ki-67 in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, there were notably positive correlations between Ki-67 and Ktrans values. Consistent with our results, Kim et al found that the Ktrans values in breast cancer with Ki-67 overexpression were significantly higher in patients with low expression of Ki-67 [38]. However, unlike Kim et al’s study, there was no correlation between Kep value and Ki-67 in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Breast cancer patients with ER- and PR-positive are sensitive to endocrine therapy, the survival rate is high, and the prognosis is relatively good [38]. When the ER and PR expression was negative, more contrast agent backflows from extravascular and extracellular space back to the tumor capillary cavity, indicating the capillary permeability is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Pooling the data revealed that a positive pan-ERβ status was associated with an improved DFS (HR=0.51, 95%CI 0.35-0.75, P =0.0007; heterogeneity: P =0.33, I^2=9%; Figure S1 ). Five studies [ 4 , 9 , 12 , 20 , 24 ] assessed ERβ mRNA levels via PCR, and no association between total ERβ mRNA levels and DFS was detected ( Figure S2 ). Wimberly et al [ 22 ]employed a tissue microarray (TMA) to assess the pan-ERβ and ERβ-1 statuses of four independent populations.…”
Section: Resultsmentioning
confidence: 99%
“…Speirs et al [ 31 ]noted that ERβ mRNA levels were increased in tamoxifen-resistant breast cancer patients. Similarly, Kim et al [ 9 ] reported that a higher ERβ mRNA level is associated with poorer DFS in patients treated using endocrine therapy. We believe that the assessment of ERβ status based on mRNA levels may be inaccurate because samples from breast tissue might contain cells from surrounding cancerous tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Esslimani-Shaha et al ascribe the progression of the malignancy and tamoxifen resistance to the decreased expression of ERb (Shaaban et al 2003, Esslimani-Sahla et al 2004, Hopp et al 2004. However, there are also studies which show high ERb expression in ductal cancer and in these studies, ERb expression is associated with poor prognosis (Markey et al 2009, Kim et al 2012. The reasons for the reported differences in the contribution of ERb to breast cancer progression will no doubt be explained as more studies are done and the antibodies used become more standardized.…”
Section: ) While Others Have Found That It Ismentioning
confidence: 92%